A European agenda for the collaborative economy - Valant, Jana (Brussels, 2016)
"The 'collaborative economy' – also known as the 'sharing economy' – enables people to share goods and services by using internet platforms and information and communications technology applications. Due to its rapid growth, the collaborative economy has recently raised regulatory issues in various sectors across the European Union (EU). It is argued that this new model of economic activity, with its focus on consuming more efficiently, brings consumers lower prices and broader choice and enables them to capitalise on their property and skills to generate extra income. A counter-argument stresses that this is causing market imbalances and unfair competition in relation to traditional market players, because of non-regulated issues related to labour standards and rights, consumer protection, taxation, liability, quality of services and user safety. To avoid a fragmented approach across the EU and growing uncertainty regarding applicable rules while trying to prevent a potential stifling of innovation, the European Commission published its guidance on the matter on 2 June 2016. 'A European agenda for the collaborative economy' is to serve as policy orientation for Member States to help ensure balanced development of the EU collaborative economy. In the European Parliament, the Internal Market and Consumer Protection Committee will draft an own initiative report on the agenda."